Sistem Informasi Absensi Siswa Berbasis Web (Studi Kasus Pada SMK Kesehatan Nasional Surakarta) - Hardiyanto, Anggit; Fitriandra, Bagas; Hastuti, Pipin Tri (Politeknik Indonusa Surakarta, 2023)
The student attendance process at the National Health Vocational School Surakarta is currently carried out manually in an attendance book. Based on this, a web-based student attendance information system has been designed to facilitate attendance and record student attendance data. The system development method used is the waterfall method, which involves stages of analysis, design, implementation, testing, and maintenance. During the analysis stage, the identification of main needs and issues in managing student attendance at the National Health Vocational School Surakarta was conducted. The results of this analysis form the basis for designing a system that meets the school's needs and characteristics. This student attendance information system is designed as a web-based application for easy access. The main functions of the system include daily attendance recording, monitoring student presence, and efficient attendance data management.